El aprendizaje y sus incidencias en las actividades intraclase de los estudiantes de noveno año de Educación Básica del Instituto Tecnológico Dr. José Ochoa León Mera del cantón Pasaje, período lectivo 2012-2014. - González González, Luis David (2014)
Traditional education has focused its learning axis on the memorization of contents, however, modern pedagogy has not been unaware of this fact and has raised new issues to improve the construction of knowledge.